Electrocardiographic left atrial abnormality and silent vascular brain injury: The Northern Manhattan Study. - Madeleine D Hunter; Yeseon Park Moon; Charles DeCarli; Jose Gutierrez; Clinton B Wright; Marco R Di Tullio; Ralph L Sacco; Hooman Kamel; Mitchell S V Elkind (PLoS ONE, 2018)
HYPOTHESIS:We hypothesized that P wave terminal Force in the V1 lead (PTFV1) would be associated with leukoaraiosis and subclinical infarcts, especially cortical infarcts, in a population-based, multi-ethnic cohort. METHODS:PTFV1 was collected manually from baseline electrocardiograms of clinically stroke-free Northern Manhattan Study participants. Investigators read brain MRIs for superficial infarcts, deep infarcts, and white matter hyperintensity volume (WMHV). WMHV was adjusted for head size and log transformed, achieving a normal distribution. Logistic regression models investigated the association of PTFV1 with cortical and with all subclinical infarcts. Linear regression models examined logWMHV. Models were adjusted for demographics and risk factors. RESULTS:Among 1174 participants with PTFV1 measurements, the mean age at MRI was 70 ± 9 years. Participants were 14.4% white, 17.6% black, and 65.8% Hispanic. Mean PTFV1 was 3587.35 ± 2315.62 μV-ms. Of the 170 subclinical infarcts, 40 were cortical. PTFV1 ≥ 5000 μV-ms was associated with WMHV in a fully adjusted model (mean difference in logWMHV 0.15, 95% confidence interval 0.01-0.28). PTFV1 exhibited a trend toward an association with cortical infarcts (unadjusted OR per SD change logPTFV1 1.30, 95% CI 0.94-1.81), but not with all subclinical infarcts. CONCLUSION:Electrocardiographic evidence of left atrial abnormality was associated with leukoaraiosis.